Green extraction of Milletia pinnata oil for the development, and characterization of pectin crosslinked carboxymethyl cellulose/guar gum herbal nano hydrogel - Bhagyashree Devidas, Tipare; Patil, Sandip; Sharma, Minaxi; Ali, Nemat; Parvez, Mohammad Khalid; Al-Dosari, Mohammed S.; Liu, Sixi; Inbaraj, Baskaran Stephen; Bains, Aarti; Wen, Feiqiu (Frontiers in Chemistry, 2023)
Milletia pinnata oil and Nardostachys jatamansi are rich sources of bioactive compounds and have been utilized to formulate various herbal formulations, however, due to certain environmental conditions, pure extract form is prone to degradation. Therefore, in this, study, a green hydrodistillation technology was used to extract M. pinnata oil and N. jatamansi root for the further application in development of pectin crosslinked carboxymethyl cellulose/guar-gum nano hydrogel. Both oil and extract revealed the presence of spirojatamol and hexadecanoic acid methyl ester. Varied concentrations (w/w) of cross-linker and gelling agent were used to formulate oil emulsion extract gel (OEEG1, OEG1, OEEG2, OEG2, OEEG3, OEG3, OEEG4, OEG4, OEEG5, OEG5), in which OEEG2 and OEG2 were found to be stable. The hydrogel displayed an average droplet size of 186.7 nm and a zeta potential of -20.5 mV. Endo and exothermic peaks and the key functional groups including hydroxyl, amide II, and amide III groups confirmed thermal stability and molecular structure. The smooth surface confirmed structural uniformity. Bactericidal activity against both Gram-positive (25.41±0.09 mm) and Gram-negative (27.25 ±0.01 mm) bacteria and anti-inflammatory activity (49.25-83.47 %) makes nanohydrogel a potential option for treating various infections caused by pathogenic microorganisms. In conclusion, the use of green hydrodistillation technology can be used to extract the bioactive compounds that can be used in formulation of biocompatible and hydrophobic nanohydrogels. Their ability to absorb targetspecific drugs makes them a potential option for treating various infections caused by pathogenic microorganisms.